Optimalisasi Pemahaman Konsep dan Aktivitas Belajar Fisika Melalui Discovery Learning Berbasis Simulasi PhET pada Materi Hukum Newton - Bui, Febriani Susanti; Naen, Alfons Bunga; Maing, Claudia Mariska M.; Freitas, Maria Lia Felizarda (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2025)
The lack of understanding of physics concepts and the low active participation of students during the learning process are the main obstacles in physics learning, especially in Newton's Law material, which requires deep conceptual understanding. This study aims to: 1) determine the improvement of students' understanding of physics concepts through the application of the discovery learning model assisted by PhET simulations in Newton's Law material at St. Rafael Oepoi Seminary Senior High School, Kupang, and 2) analyze students' learning activities during the learning process using the model. The research method used is pre-experimental with a One Group Pretest-Posttest Design. The research subjects consisted of 30 eleventh-grade students selected through purposive sampling. The research instruments included a conceptual understanding test in the form of pretest and posttest questions, as well as observation sheets for students' learning activities. The results showed a significant improvement in students' understanding of physics concepts, as indicated by an average N-Gain score of 0.79, categorized as high. Additionally, students' learning activities during discovery learning assisted by PhET simulations achieved a percentage of 90%, categorized as very high. These findings indicate that the application of the discovery learning model assisted by PhET simulations is effective in improving the understanding of physics concepts and encouraging active student participation. Therefore, the discovery learning model assisted by PhET simulations can be an alternative innovative learning strategy that is relevant for physics learning, especially in materials requiring deep conceptual understanding such as Newton's Law.